Beneficio del uso de tecnologías sostenibles para el tratamiento de aguas residuales (2016)
Wastewater treatment plants are vital facilities for the right functioning of a city, town or municipality, as the conservation of water resources and public health. The rise of sustainable technologies for treating wastewater has been great, they can be applied to all kind of place, depending on the specific characteristics of each site in terms of water quality, land available and economic capacity. Sustainable technologies provide an effective treatment, as well as the use of wastewater and products of their treatment as a resource (reuse of non-potable effluent, reuse of biogas as a producer of energy and heat, reuse of biomass for compost or generation of fuel). This work is aimed to recognize some existing sustainable technologies and to characterize their benefits. Chapter 1 presents the proposed objectives. Chapter 2 describe the conventional technologies for wastewater treatment. Chapter 3 presents the applied criteria of sustainability and the definition of appropriate and sophisticated technologies for wastewater treatment. Chapter 4 shows the main qualities about some of the sustainable technologies of wastewater treatment. Chapter 5 relates some of the cases of sustainable technologies of wastewater treatment. Finally, Chapter 6 presents the relevant conclusions.